Evaluation of Swedish Youth Labour Market Programmes - Laura Larsson (Uppsala University, Department of Economics, 2000)
This paper evaluates two Swedish active labour market programmes for youth, namely youth practice and labour market training. A non-parametric matching approach is applied to estimate the average program effects. Moreover, the results obtained by matching are compared to results from standard linear regression and probit models, and a polychotomous selectivity model. The results indicate either zero or negative effects of both programmes on earnings, re-employment probability and probability of studies in the short run, whereas some of the long-run effects are estimated positive. However, there is much heterogeneity in the estimated treatment effects among the individuals.
Keywords: C14; C50; J38; J68; 330; Active labour market policies; balancing score; evaluation; matching; propensity score; selection; treatment effects; Junge Arbeitskräfte; Arbeitsmarktpolitik; Projektbewertung; Schweden